Nepal Journal of Medical Sciences (NJMS) Declaration Form - Editor, The (Nepal Journal of Medical Sciences, 2013)
Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 DOI: http://dx.doi.org/10.3126/njms.v2i2.8980